Case Report: A Rare Case of Pembrolizumab-Induced Bullous Pemphigoid - Zhang, Xiaoyan; Sui, Dongjiang; Wang, Dong; Zhang, Lina; Wang, Ruiyan (Frontiers in Immunology, 2021)
PD-1 inhibitor pembrolizumab is the most widely used immune checkpoint inhibitor in the world. Pmbrolizumab may abnormally enhance the normal immune response, destroy the balance of the immune environment, and may lead to toxic reactions similar to autoimmune diseases. Sometimes serious adverse events may occur. However, it has not been reported that pembrolizumab caused bullous pemphigoid. Here, we described a rare case of pembrolizumab-induced bullous pemphigoid. A 79-year-old male patient presented with scattered erythema, papules, blisters and pruritus after treatment with pembrolizumab. Then the rash gradually aggravated and spread to the whole body. Extensive edematous erythema, blisters, bullae, blood blisters, bullae were loose and easy to rupture, forming an erosive surface, and with pruritus and obvious pain. Histopathological diagnosis was bullous pemphigoid. Consider the possibility of pemphigoid caused by pembrolizumab. After glucocorticoid treatment, the ras gradually improved. Therefore, in the course of pembrolizumab treatment of tumor, we should also pay attention to the occurrence of skin adverse reactions, pay attention to the characteristics, clinical manifestations, pathological characteristics and treatment principles of bullous pemphigoid, so as to reduce the risk of prognosis and prolong the survival period.